The development of neurocritical care in China from the perspective of evaluation and treatment of critical neurological diseases - Su, Yingying; Teng, Junfang; Tian, Fei; Jing, Jing; Huang, Huijin; Pan, Suyue; Jiang, Wen; Wang, Furong; Zhang, Le; Zhang, Yan; Zhang, Meng; Liu, Liping; et al. (Frontiers in Neurology, 2023)
Objective To understand the varieties, evaluation, treatment and prognosis of severe neurological diseases using the third NCU survey in China. Design A cross-sectional questionnaire study. The study was completed in three main steps: filling in the questionnaire, sorting out the survey data and analyzing the survey data. Results Of 206 NCUs, 165 (80%) provided relatively complete information. It was estimated that 96201 patients with severe neurological diseases were diagnosed and treated throughout the year, with an average fatality rate of 4.1%. The most prevalent severe neurological disease was cerebrovascular disease (55.2%). The most prevalent comorbidity was hypertension (56.7%). The most prevalent complication was hypoproteinemia (24.2%). The most common nosocomial infection was hospital-acquired pneumonia (10.6%). The GCS, APACHE II, EEG and TCD were the most commonly used (62.4%-95.2%). The implementation rate of the five nursing evaluation techniques reached 55.8%~90.9%. Routinely raising the head of the bed by 30°, endotracheal intubation and central venous catheterization were the most prevalent treatment strategies (97.6%, 94.5% and 90.3%, respectively). Traditional tracheotomy, invasive mechanical ventilation and nasogastric tube feeding (75.8%, 95.8% and 95.8%, respectively) were more common than percutaneous tracheotomy, noninvasive mechanical ventilation and nasogastric tube insertion (57.6%, 57.6% and 66.7%, respectively). Body surface hypothermia brain protection technology was more commonly used than intravascular hypothermia technology (67.3%>6.1%). The rates of minimally invasive hematoma removal and ventricular puncture were only 40.0% and 45.5%, respectively. Conclusion In addition to traditional recognized basic life assessment and support technology, it is necessary to the use of promote specialized technology for neurological diseases, according to the characteristics of critical neurological diseases.